Factors affecting the structure and maintenance of phytoplankton functional groups in a nutrient rich lowland river - Devercelli, M. (2013)
The phytoplankton structure along the mainstem of the Lower Salado River (Argentina) was analysed in relation to the environmental variables and the influence exerted by the inflowing waters from the Paraná River (via El Vado Stream) and an adjacent floodplain shallow lake, between December 2003 and August 2004. Phytoplankton driving forces were explored using a functional approach. Small phytoplanktonic organisms with high metabolism and well adapted to live in mixed environments dominated (functional groups C, D, X1, X2), but the organic enrichment and slow flow also facilitated the thriving of Cyanobacteria (LO and minor contributions of H1, K, SN) and large Euglenophyta (W1, W2) inflowing from adjacent sites. The longitudinal and temporal changes in the phytoplankton structure depended on the prevailing hydrological conditions. Three scenarios were identified as regards the complex hydrological interactions of the Paraná and Salado Rivers: (i) the hydrological isolation period (low waters) when the Salado had a homogeneous longitudinal pattern and high phytoplankton development; (ii) the period of hydrological interactions with Salado River influence (high waters) when the homogeneous longitudinal pattern extended to the stream, and algal growth in the river was counteracted by dilution and enhancement of water velocity, and (iii) the period of hydrological interactions with Paraná System influence characterised by a longitudinal discontinuity with lower phytoplankton concentrations downriver the Paraná inflow due to dilution. There were no evidences that the lake contributed with algal biomass to the downriver plankton during the study period. © 2012 Elsevier GmbH.